login
a(n) = a(n-1) + a(n-2) + a(n-4) with a(0) = 2, a(1) = 3, a(2) = 6, a(3) = 9.
1

%I #6 Jul 14 2018 16:06:04

%S 2,3,6,9,17,29,52,90,159,278,489,857,1505,2640,4634,8131,14270,25041,

%T 43945,77117,135332,237490,416767,731374,1283473,2252337,3952577,

%U 6936288,12172338,21360963,37485878,65783129,115441345,202585437

%N a(n) = a(n-1) + a(n-2) + a(n-4) with a(0) = 2, a(1) = 3, a(2) = 6, a(3) = 9.

%H Harvey P. Dale, <a href="/A095982/b095982.txt">Table of n, a(n) for n = 0..1000</a>

%H <a href="/index/Rec#order_04">Index entries for linear recurrences with constant coefficients</a>, signature (1,1,0,1).

%t LinearRecurrence[{1,1,0,1},{2,3,6,9},40] (* _Harvey P. Dale_, Jul 14 2018 *)

%K easy,nonn

%O 0,1

%A P. Barkin (prb614(AT)comcast.net), Jul 16 2004

%E Corrected and extended by _Ray G. Opao_, Aug 09 2004